Exploring the Effect of Dehydration on Water Migrating Property and Protein Changes of Large Yellow Croaker (Pseudosciaena crocea) during Frozen Storage - Mingtang Tan; Jing Xie (Foods, 2021)
This study aimed to explore the effect of dehydration on the water migrating property and protein changes of large yellow croaker during frozen storage. A freeze-dryer was used to accelerate experiments, which was isolated from oxygen and excluded the effects of protein oxidation. After dehydration time (3, 9, 18, and 30 h) for both fast- and slow-freezing samples, the results showed that the ice sublimation of samples containing small ice crystals was faster than that of samples containing large ice crystals in the early stages of dehydration, but in the latest stage, there was an opposite trend. The results indicated that dehydration reduced the water freedom degrees and water–protein interaction. At the same time, dehydration had a significant effect on protein secondary and tertiary structures. The significant increase in surface hydrophobicity and particle size indicated that dehydration exacerbated myofibrillar protein aggregation. The ΔH1 values (from 1.275 to 0.834 J/g for slow-freezing group and from 1.129 to 0.855 J/g for fast-freezing group) decreased gradually as the dehydration time extended, indicating the decrease in protein thermal stability. Additionally, significant protein degradation occurred when the water content of the sample decreased to a certain level. This study showed that ice crystal size had an important effect on the rate of ice sublimation, and the occurrence of dehydration during frozen storage accelerated the water loss and the decrease in protein stability.